KEEFEKTIFAN DAN STRATEGI ORGANISASI: SUATU TINJAUAN SURVEY LITERATUR - Ahadiat, Ayi (JURNAL BISNIS STRATEGI, 2003)
The effectiveness becomes an importance issue in the organization theory because it discusses how an organization can successfully run its strategy. The objective of this article is to conceptually elaborate the effectiveness and its relation to organization strategy. Descriptive analysis on effectiveness covers topics ranging from definition, model, criterion, and measurement problems. Descriptive analysis on strategy discusses the relation strategy with effectiveness, how consistent the organization strategy with its effective implementation. To elaborate strategy topic, article also discusses the evolution of organization and the effectiveness that relate to the strategy and structure. The conclusion shows that organization will become effective if it is supported by strategy, structure and process, this because the effectiveness is an element of structure and process of strategy.